EVALUASI TINGKAT PELAYANAN BEBERAPA RUAS JALAN DI SEKITAR JALAN SIS AL JUFRI KOTA PALU - Mashuri, Mashuri; Patunrangi, Jurair (MEKTEK, 2012)
The discourse made along Jl. Sis Aljufri as theÂ  religious area tourism is a program to encourage the development of tourism sector and preservation of Islamic culture in Palu. In the area Plan, certain events are planned at the Jl. Sis Aljufri done closure of vehicular traffic flow so that all vehicles will enter the religion area throughÂ  Jl. Sis Aljufri will be transferred to some streets in the surrounding. Traffic volume data obtained through a survey of traffic volume.The survey of traffic volume at peak morning and evening has been done working day in June 2012. The purpose of this study was to determine the level of service Jl. Mangga, Jl. Datu Pamusu, Jl. S. Sausu and Jl. S. Moutong both existing conditions and current conditions of the transfer of traffic flow on Jl. Sis Aljufri.Methods of traffic data collection is done manually by recording vehicles passing on a road during peak hours. Methods of data collection side friction done manually by recording the vehicle stops, the slower vehicles, the pedestrians, vehicles in and out of the side of the road. The results of this study found that the road gets traffic diverted due to the closure of Jl. Sis Aljufri increased degree of saturation, which means a change in level of service.